Smart homes system / Nurfitrah Abdul Aziz and Alyaa Ainaa Abdullah - Abdul Aziz, Nurfitrah; Abdullah, Alyaa Ainaa (2015)
According to Maslow's hierarchy of needs, shelter are being categorized as physiological needs. It is the basic needs of a normal human being. A house or a home is crucial for human being to take shelter. Even though houses are being built for human needs, conventional houses doesn't include automated system and security system. Thus this project main intention is to provide a smart home system where the system consist of automated and security system for conventional houses. The main features of this system lies on its dual systems where it can be changed to automate or security system by a click of a switch. A small scale house will be model to replicate the smart system and arduino will be used to control the smart system. It is hoped that this system will give and idea to install the system in a real house because people are willingly to invest for comfort and convenience and security of their house because as a Malay idiom stated that my house is my heaven.